2001
DOI: 10.1021/bc010003g
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged in Vivo Residence Times of Antibody Fragments Associated with Albumin

Abstract: Antibody fragments can be expressed at a high level in microbial systems, but they may have limited therapeutic value because they are rapidly eliminated from the body. We demonstrate here that site-specific conjugation or binding of bacterially derived Fab' to the long-lived protein serum albumin allows full retention of the antibody's binding characteristics while imparting the albumin's longevity in vivo. In rats the area under the curve for Fab' conjugated to rat serum albumin was 17-fold greater than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 14 publications
4
63
0
Order By: Relevance
“…Kidneys (8.1±0.4 %ID/g at 0 hr) and spleen (6.6±0.5 %ID/g at 18 hr) had limited activity. Pharmacokinetic studies showed the [ 125 I]-and [ 111 In]-DOTA-versions had nearly identical blood clearance activity of radiolabel (T 1/2 α≈1 hr and T 1/2 β≈15 hr), which were comparable to the half-lives observed for an anti-TNF scFv-HSA fusion protein [2].…”
Section: Biodistribution Studies With [ 125 I]-t8466 Immunobumin Andmentioning
confidence: 84%
See 2 more Smart Citations
“…Kidneys (8.1±0.4 %ID/g at 0 hr) and spleen (6.6±0.5 %ID/g at 18 hr) had limited activity. Pharmacokinetic studies showed the [ 125 I]-and [ 111 In]-DOTA-versions had nearly identical blood clearance activity of radiolabel (T 1/2 α≈1 hr and T 1/2 β≈15 hr), which were comparable to the half-lives observed for an anti-TNF scFv-HSA fusion protein [2].…”
Section: Biodistribution Studies With [ 125 I]-t8466 Immunobumin Andmentioning
confidence: 84%
“…Since the first three residues of HSA were not visible in the crystal structure, they were deleted rather than fusing the scFv directly to the amino-terminus of the mature HSA as previously reported [2].…”
Section: Molecular Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither molecule shows more than half the serum persistence of endogenous rat albumin (56). Notably, mouse and rat FcRn HCs showed high homology (89%) (supplemental Table 3), as did rat and mouse albumin sequences (90%).…”
Section: Discussionmentioning
confidence: 98%
“…This has value if the domain is designed to be an in vivo imaging agent where signal--to-noise ratios determine assay sensitivity but can be potentially limiting for the development of an efficacious drug. There are multiple ways to improve the pharmacokinetic profile of small proteins or peptides [69][70][71][72][73][74][75][76][77][78][79][80]. Fusion to an antibody Fc domain, as mentioned previously, is one way [81]; however, if being small is advantageous, then adding multiple extra domains (Fc) counteracts this size benefit.…”
Section: Drug Developmentmentioning
confidence: 99%